Situation Report: Romania, 24 February 1986 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Ceausescu at 68 / by Anneli Maier Romania Responds to Western Criticism of Urban Demolition / by Dan Ionescu Romanian-Hungarian Invective Reaches New Level / by Anneli Maier A Chemical-Weapons-Free-Zone in the Balkans? The Economic Malaise Worsens / by Paul Gafton Heavy Snowfall Raises the Specter of Winter Hardship / by Paul Gafton Soviet-Romanian Industrial Cooperation and Trade / by Vladimir Socor Bureaucratic Hurdles Discourage Foreign Travel / by Rene Al. de Flers Orthodox Priest Speaks Out against Religious Oppression / by Dan Ionescu